Photostimulus-responsive large-area two-dimensional covalent organic framework films - Yu, Fei (2020)
Using an external stimulus to modulate the electronic structure of covalent organic frameworks (COFs) is very important because such a response will endow them with additional functions. A two-dimensional (2D) COF, constructed from a photo-responsive unit (1,2-bis(5-formyl-2-methylthien-3-yl)cyclopentene), can reversibly switch its electrical conductivity 200 times from low state (the open form) to high state (the closed form) upon irradiation with UV light and reversible with visible light. This reversible phenomenon can be monitored through a circuit containing a light-emitting diode (LED). Photoinduced ring-closing/opening reactions do not destroy the integrity of the frameworks, and both processes follow logarithmic carrier generation with time. Moreover, the correlation between COFs electronic properties and changes in photoinduced kinetics and absorption curves has been demonstrated.